Formulasi dan Evaluasi Uji Stabilitas Fisik Tablet Limbah Cangkang Kerang Gonggong - Suhaera Suhaera; Suci Fitriani Sammulia; Reny Haryani; Shinta Sari Dewi (Pusat Riset dan Inovasi Nasional, 2021)
Snail Gong-gong (Strombus Turturella) is a typical food of the people of Riau Islands. The processed food produces the waste of a well-utilized shell. The main composition of the gong-gong slug is calcium carbonate (CaCO3). With the content of calcium, the waste shell of gong-gong can be used as raw material for the preparation of pharmaceutical preparations such as suction tablets. This study aims to obtain the formulation of a lozenges from the waste of gong-gong shell with good physical properties. A lozenges is made by a method of wet granulation in three formulas with variations in the concentrations of the case of the F1 gong-gong 15%, F2 30%, and F3 45%. The granules and tablets are evaluated. The results of the granule evaluation showed that the granule produced from the three formulas has fulfilled the requirements, the results of the tablet evaluation showed on organoleptic test, size uniformity, hardness, disintegration time of all three formulas have fulfilled good lozenges requirements. While the weight uniformity of F1 is not eligible, the friability test F1 and F2 are not eligible. The results of this study showed that the gong-gong snail shells can be formulated into a lozenges and have good physical properties.